An Algorithm for On‐line Measurement of the Internal Resistance of Proton Exchange Membrane Fuel Cell. Issue 2 (2nd April 2015) - Chen, F.; Gao, Y.
Abstract The internal resistance of proton exchange membrane fuel cell (PEMFC) system is difficult to measure on‐line due to its variation with time. The traditional electrochemical impedance spectroscopy (EIS) and its variants such as high frequency resistance (HFR) can be used to measure the resistance when the system is in steady state, but they fail in automotive applications where a change in speed or inclination modifications could lead to a sharp fluctuation in demand on power. In order to resolve this problem, a novel algorithm is proposed in this paper to estimate the resistance based on the alternating current (AC) impedance spectroscopy technique by adding an extra term to eliminate the errors caused by voltage variation or when the system is under unsteady state. Numerical simulations show that the proposed algorithm can not only accurately track the variation of the internal resistance, but is also robust against the noises caused by uncertainty and measurements.